From Agricultural Waste to Construction Material: The Necessity of Controlled Water Curing for CLR-Concrete (Journal of Civil Engineering Researchers, 2026)
The sugar industry generates substantial agricultural waste, necessitating sustainable recycling pathways. This study explores the valorization of Carbonation Lime Residue (CLR), a waste from sugar beet processing, in concrete as a partial cement replacement. Given the critical impact of curing on performance, this research specifically investigates the effect of curing conditions on CLR-based concrete. Specimens with 0% to 40% CLR were prepared and subjected to two distinct curing regimes: stagnant water and controlled curing with periodic water replacement. Compressive strength was evaluated at 7, 28, 56, and 90 days, while the curing water was monitored for electrical conductivity (EC) and total dissolved solids (TDS). The results revealed that stagnant water curing led to a sharp decline in long-term strength, attributed to the leaching of impurities and a consequent harmful increase in water salinity. Conversely, controlled water curing with periodic refreshing prevented salt accumulation and facilitated a continuous strength gain for all mixes. A 20% cement replacement with CLR was found to be structurally viable under this proper curing method. This study conclusively demonstrates that controlled water curing is not merely beneficial but essential for producing durable green concrete from agricultural waste, effectively transforming it into a valuable construction material.
Keywords: Carbonation Lime Residue (CLR); Curing Conditions; Green Concrete; Compressive Strength; Agricultural Waste